Wakefields excitation in plasma, produced by a sequence of electron bunches in neutral gas, accelerating and focusing electrons by them - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I. (Вопросы атомной науки и техники, 2011)
Experiments on wakefield excitation by a long sequence of relativistic electron bunches in plasma, formed by head bunches of the same sequence in neutral gas of various pressure are presented. The ranges of pressure are found, in which beam-plasma discharge is developed, that leads to intensification of plasma generation. Acceleration and focusing of bunches electrons that is determined by ratio of the bunch length to its diameter and detuning between bunches repetition frequency and wakefield frequency, are investigated.